2018
DOI: 10.1038/s41598-018-33761-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of p53-binding protein 1 as a new molecular indicator of genomic instability in bladder urothelial carcinoma

Abstract: Copy number alterations and loss of heterozygosity are associated with increasing tumor grade and bladder cancer stage. Our previous study suggested that co-expression of Ki-67 and p53-binding protein 1 (53BP1) could provide an indicator of an abnormal DNA damage response (DDR) pathway. The present study investigated 53BP1 expression as a novel molecular marker in urothelial carcinoma (UC) using bladder tissues with in total of 40 cases including a normal urothelium, urothelial papilloma, low-grade UC, or high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…2). With the hypothesis that the presence of 53BP1 NF can be an indicator of endogenous DNA double-strand breaks and DDR activation in individual cells, we previously demonstrated that the type of 53BP1 expression profiles determined by IF may be useful to estimate GIN during a divergent carcinogenesis in thyroid, skin, uterine cervix, bladder, and esophageal cancer ( 7 , 8 , 9 , 10 , 11 ). Classification of 53BP1 expression into the following five categories: (i) stable (no or faint staining); (ii) low DDR (one or two discrete NF); (iii) high DDR (three or more discrete NF); (iv) large focus (discrete NF ≥1 μm and (v) diffuse (intense and heterogenous expression), showed that both the high DDR and large focus types are closely associated with a higher level of cervical carcinogenesis and high-risk human papilloma virus infection ( 9 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2). With the hypothesis that the presence of 53BP1 NF can be an indicator of endogenous DNA double-strand breaks and DDR activation in individual cells, we previously demonstrated that the type of 53BP1 expression profiles determined by IF may be useful to estimate GIN during a divergent carcinogenesis in thyroid, skin, uterine cervix, bladder, and esophageal cancer ( 7 , 8 , 9 , 10 , 11 ). Classification of 53BP1 expression into the following five categories: (i) stable (no or faint staining); (ii) low DDR (one or two discrete NF); (iii) high DDR (three or more discrete NF); (iv) large focus (discrete NF ≥1 μm and (v) diffuse (intense and heterogenous expression), showed that both the high DDR and large focus types are closely associated with a higher level of cervical carcinogenesis and high-risk human papilloma virus infection ( 9 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Classification of 53BP1 expression into the following five categories: (i) stable (no or faint staining); (ii) low DDR (one or two discrete NF); (iii) high DDR (three or more discrete NF); (iv) large focus (discrete NF ≥1 μm and (v) diffuse (intense and heterogenous expression), showed that both the high DDR and large focus types are closely associated with a higher level of cervical carcinogenesis and high-risk human papilloma virus infection ( 9 , 13 ). Instead, both large focus and diffuse types are significantly associated with high-grade urothelial carcinoma showing chromosomal instability and poor prognosis ( 10 ). Moreover, in a rare case of uterine dedifferentiated leiomyosarcoma arising from leiomyoma, we observed that the diffuse 53BP1 expression was restricted only to the sarcoma component, and frequently co-localized with p53 overexpression in sarcoma cells, including highly atypical multinucleated giant cells, suggesting aneuploidy ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, a positive correlation between CD133 and Ser20 expression was observed in ovarian carcinomas. The use of double immunostaining technique allows to reveal the co-expression between p-p53(Ser20) and CD133 molecules in single ovarian carcinoma cell [34,35]. The co-expression of p-p53(Ser20) and CD133 molecule was found in ovarian carcinomas with nuclear p53 protein expression, but also was observed in cases without p53 protein expression detected by DO-7 antibody.…”
Section: Discussionmentioning
confidence: 99%